Novos táxons de Apomecynini (Coleoptera, Cerambycidae, Lamiinae) - Martins, Ubirajara R.; Galileo, Maria Helena M. (Papéis Avulsos de Zoologia, 2008)
New taxa on Apomecynini (Coleoptera, Cerambycidae, Lamiinae). New taxa described: Tethystola cincta sp. nov. and Rosalba formosa sp. nov. from Bolívia (Santa Cruz); Adetus stellatus sp. nov. from Costa Rica (Cartago); Acrepidopterum capilosum sp. nov. from Honduras (Ilha Roatán); Irundiaba gen. nov. type species, I. waorani sp. nov. from Ecuador (Napo). A new name, Neopoticatuca is proposed to Potiatuca Martins & Galileo, 2007 (Cerambycinae, Ibidionini) non Potiatuca Galileo & Martins, 2006 (Lamiinae, Apomecynini); Neopotiatuca brevis (Martins & Galileo, 2007) comb. nov.